2020
DOI: 10.1007/s12678-019-00577-8
|View full text |Cite|
|
Sign up to set email alerts
|

Alkaline Ethanol Oxidation Reaction on Carbon Supported Ternary PdNiBi Nanocatalyst using Modified Instant Reduction Synthesis Method

Abstract: Direct ethanol fuel cells (DEFC) still lack active and efficient electrocatalysts for the alkaline ethanol oxidation reaction (EOR). In this work, a new instant reduction synthesis method was developed to prepare carbon supported ternary PdNiBi nanocatalysts with improved EOR activity. Synthesized catalysts were characterized with a variety of structural and compositional analysis techniques in order to correlate their morphology and surface chemistry with electrochemical performance. The modified instant redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…The catalyst ink was prepared by dispersing the electrocatalysts in a mixture of 2-propanol (99.9% p.a., Roth) and distilled water (7:3) containing 30 wt.% of a commercial anion exchange ionomer (fumion ® FAA-3 solution in NPM, 10%). The cathode was prepared by spraying the ink slurry of a commercial PtRu/C catalyst (Platinum, nominally 40%, Ruthenium, nominally 20% on carbon black, HiSPEC ® 10000) onto a carbon paper as GDL (Sigracet 29 BC, fuel cell store, 0.235 mm thick), whereas an ink of a PdNiBi/C catalyst synthesized by the modified instant reduction method [ 16 ] was sprayed on a carbon cloth (ELAT—hydrophilic plain cloth, fuel cell store, 0.406 mm thick) to fabricate the anode. The electrode preparation resulted in a metal loading of 0.5 mg cm −2 for the cathode and 0.75 mg cm −2 for the anode.…”
Section: Methodsmentioning
confidence: 99%
“…The catalyst ink was prepared by dispersing the electrocatalysts in a mixture of 2-propanol (99.9% p.a., Roth) and distilled water (7:3) containing 30 wt.% of a commercial anion exchange ionomer (fumion ® FAA-3 solution in NPM, 10%). The cathode was prepared by spraying the ink slurry of a commercial PtRu/C catalyst (Platinum, nominally 40%, Ruthenium, nominally 20% on carbon black, HiSPEC ® 10000) onto a carbon paper as GDL (Sigracet 29 BC, fuel cell store, 0.235 mm thick), whereas an ink of a PdNiBi/C catalyst synthesized by the modified instant reduction method [ 16 ] was sprayed on a carbon cloth (ELAT—hydrophilic plain cloth, fuel cell store, 0.406 mm thick) to fabricate the anode. The electrode preparation resulted in a metal loading of 0.5 mg cm −2 for the cathode and 0.75 mg cm −2 for the anode.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we showed that the presence of ethanol could change the FAO oxidation mechanism and inhibits the IDPW. However, the long-term instability of Pd/C catalyst in acidic media 29,40,41 makes it difficult to differentiate between the catalyst poisoning versus catalyst instability as a reason behind the Pd catalyst deactivation with cycling, using CV technique. catalyst is found to lose 58.5, 33.3, and 16.5% of its surface area aer 100 cycles when the 0.39, 0.05, and À0.3 V were used as upper potential, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of the blend on the presence/absence of the FA IDPW was not clear since the formic acid concentration was low (0.3 M). Pallidum is one of the most active metals towards (EOR) in alkaline medium, [26][27][28][29] however it is inactive towards ethanol oxidation reaction (EOR) in acidic medium. [30][31][32][33] As shown in (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the carbon support helped in the fine dispersion of nanoparticles, increased the number of active sites and controlled the particle size and their distribution. 125 …”
Section: Materials For the Ethanol Oxidation Reactionmentioning
confidence: 99%